2019
DOI: 10.3390/ijms20123023
|View full text |Cite
|
Sign up to set email alerts
|

OsMKK3, a Stress-Responsive Protein Kinase, Positively Regulates Rice Resistance to Nilaparvata lugens via Phytohormone Dynamics

Abstract: Plants undergo several but very precise molecular, physiological, and biochemical modulations in response to biotic stresses. Mitogen-activated protein kinase (MAPK) cascades orchestrate multiple cellular processes including plant growth and development as well as plant responses against abiotic and biotic stresses. However, the role of MAPK kinases (MAPKKs/MKKs/MEKs) in the regulation of plant resistance to herbivores has not been extensively investigated. Here, we cloned a rice MKK gene, OsMKK3, and investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…BPH is a phloem feeder which causes substantial yield losses and is among the most damaging rice pests on earth (Heong, Cheng, & Escalada, 2016). Although rice plants can activate a variety of defense signaling molecules, including MPKs, WRKYs, JA, SA, ET and H 2 O 2 , and then produce defense responses when infested by BPH (Hu et al, 2016;Li, Liu, et al, 2019;Lu et al, 2014;Ma et al, 2020;Zhou et al, 2009Zhou et al, , 2019, BPH can also circumvent and suppress host plant resistance in several ways (Ji et al, 2017;Ye et al, 2017). BPH can, for instance, secrete salivary endo-β-1,4-glucanase to overcome plant cell wall defense in rice without inducing defense-related signal molecules (Ji et al, 2017), and can inhibit H 2 O 2 production in rice via reducing cellular Ca 2+ levels by secreting salivary calcium-binding proteins (Ye et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…BPH is a phloem feeder which causes substantial yield losses and is among the most damaging rice pests on earth (Heong, Cheng, & Escalada, 2016). Although rice plants can activate a variety of defense signaling molecules, including MPKs, WRKYs, JA, SA, ET and H 2 O 2 , and then produce defense responses when infested by BPH (Hu et al, 2016;Li, Liu, et al, 2019;Lu et al, 2014;Ma et al, 2020;Zhou et al, 2009Zhou et al, , 2019, BPH can also circumvent and suppress host plant resistance in several ways (Ji et al, 2017;Ye et al, 2017). BPH can, for instance, secrete salivary endo-β-1,4-glucanase to overcome plant cell wall defense in rice without inducing defense-related signal molecules (Ji et al, 2017), and can inhibit H 2 O 2 production in rice via reducing cellular Ca 2+ levels by secreting salivary calcium-binding proteins (Ye et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…DsMEK1-X1 and DsMEK1-X2 were categorized into subfamily B, which contains AtMKK3 and OsMKK3 suggesting that DsMEK1-X1 and DsMEK1-X2 possessed the close evolutionary relationship with AtMKK3 and OsMKK3. Previous studies revealed that AtMKK3 was induced by ABA or salt stress treatments [30], and treatment with methyl jasmonate (MeJA) or salicylic acid (SA) could induced the expression of OsMKK3 [31]. Thus, the phylogenetic tree analysis suggested that DsMEK1-X1 and DsMEK1-X2 may involve in abiotic stress.…”
Section: Results Cdna Cloning and Sequence Analysis Of The Dsmek1 Genementioning
confidence: 99%
“…DsMEK1-X1 and DsMEK1-X2 were categorized into subfamily B, which contains AtMKK3 and OsMKK3, suggesting that DsMEK1-X1 and DsMEK1-X2 possessed a close evolutionary relationship with AtMKK3 and OsMKK3. Previous studies revealed that AtMKK3 was induced by ABA or salt stress treatments [25], and treatment with methyl jasmonate (MeJA) or salicylic acid (SA) could induce the expression of OsMKK3 [26]. Thus, the phylogenetic tree analysis suggested that DsMEK1-X1 and DsMEK1-X2 may be involved in abiotic stress.…”
Section: Cdna Cloning and Sequence Analysis Of The Dsmek1 Genementioning
confidence: 99%